Iowa Birdline update, November 20, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for November 20, 1989. Highlights include sightings of a California Gull and Trumpeter and Tundra Swans. Epson - sheet feed/flatbed